Photodynamic therapy with verteporfin in paediatric and young adult patients: long-term treatment results of choroidal neovascularisations. Issue 5 (20th March 2008) - Lipski, A; Bornfeld, N; Jurklies, B
Abstract : Background: Vision impairment in children and young adults may derive from choroidal neovascularisation (CNV) related to numerous conditions. The aim of this study is to highlight the applicability of photodynamic therapy using verteporfin (PDT) in these patients. Methods: In 16 eyes of 16 consecutive patients aged 30 years or younger, prospective open-label PDT was performed. Outcomes of visual acuity as well as changes in CNV lesion parameters were evaluated. Results: The mean patient age at first PDT was 19.7 (SD 8.7) years (range 6–30). 81% of the patients retained stable vision within two lines or exceedingly improved vision during follow-up of 34 (24) months. Significant vision gain was denoted in seven paediatric patients (2.7 (1.4) lines, mean (SD); p = 0.019) as well as in a subgroup of 12 patients not affected by active uveitis (2.6 (2.0) lines, p = 0.0005). Two patients with multifocal choroiditis and panuveitis (MCP) experienced vision losses of five and 11 lines after four PDT sessions despite receiving additional steroidal treatment. Except for one patient with MCP and two patients who dismissed follow-up, a mean of 2.2 (1.3) PDTs per patient sufficiently inactivated CNV lesions during follow-up. In the area of the former PDT spot, alterations of the pigment epithelium increased by 40% without correlation to changes in vision. Conclusions: The results indicate good PDT efficacy and tolerability most promising in a subgroup of patients with vision-impairing CNV not associated with active uveitis. PDT in young patients with CNV remains a valuable treatment with good risk–benefit profile over the long term.